Implementasi Teknologi QR-Code Untuk Kartu Identitas - Akhmad Qashlim; Hasruddin Hasruddin (JURNAL ILMU KOMPUTER, 2015)
Abstract The need for information requires an place and certainly many people will give priority to the effectiveness and efficiency. QR-Code is able to accommodate a lot of information and can be placed in a small space such as passport, visa and id card. This study proposes a technology implementation QR-Code using the Microsoft Excel 2013, the validity of the testing performed using a QR-Code generated online recommended by Denso Wave. The results showed a QR-Code technology implementations that will allow students to check the update of real data about personal identity, status history lectures, and study history. QR-Code printed on the identity card and can be identified by electronic devices that support the reading of the QR-Code. The contribution of this study is to explore a new concept in student information services through the implementation of a student card that stores a lot of information on the QR-Code is small. Keyword: QR-Code, Kartu Identitas